Prevalence of depression and its associated factors among Chinese elderly people: A comparison study between community-based population and hospitalized population. (30th September 2016) - Li, Ning; Chen, Gong; Zeng, Ping; Pang, Jing; Gong, Huan; Han, Yiwen; Zhang, Yan; Zhang, Enyi; Zhang, Tiemei; Zheng, Xiaoying
Abstract: Depression is common among elderly people, but people from various study settings were at different levels of risk for depression. However, most of the existing studies were conducted among community population, and little was known about depression among institutionalized population. In this study, using a national sample, we aimed to compare the prevalence rate of depression and its associated factors between community-dwelling elderly people (CDEP) and elderly medical inpatients (EMI). Data for this study was derived from a national survey of the 2011 Comprehensive Assessment of Elderly Health. The Geriatric Depression Scale was used to assess depression. The results indicated that the prevalence rate of depression among EMI was significantly higher than that in CDEP (18.1% vs 11.6%, P <0.001). Physical health status was found to be the most important factor associated with depression among both groups. This study revealed a high prevalence rate of depression among Chinese elderly people, especially for those medically institutionalized. It's essential to pay more efforts on the training of general practitioners for early screening and identification of depression on the admission of elderly patients and during their hospitalization, and case management of the elderly medical inpatients on assessment and treatment for depression may be beneficial. Highlights: A comparison on depression between community-dwelling elderly people and elderly medical inpatients was conducted. Physical health status was found to be the most important factor associated with depression. For elderly medical inpatients education attainment was found to be an important predictor. Training of general practitioners for early screening and identification of geriatric depression is essential.